2020
DOI: 10.1192/bjb.2020.122
|View full text |Cite
|
Sign up to set email alerts
|

Scaling-up Health-Arts Programmes: the largest study in the world bringing arts-based mental health interventions into a national health service

Abstract: SummaryThe Scaling-up Health-Arts Programme: Implementation and Effectiveness Research (SHAPER) project is the world's largest hybrid study on the impact of the arts on mental health embedded into a national healthcare system. This programme, funded by the Wellcome Trust, aims to study the impact and the scalability of the arts as an intervention for mental health. The programme will be delivered by a team of clinicians, research scientists, charities, artists, patients and healthcare professionals in the UK's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Overall, SHAPER has three primary aims: (1) to successfully embed each of the art interventions into the healthcare system (ie, taking a social prescribing approach), (2) to scale up these interventions at a larger scale and (3) to facilitate these interventions being commissioned by Clinical Commissioning Groups (CCGs), ensuring the long-term sustainability of delivery. 15 Stroke Odysseys Rosetta Life, a well-established non-profit organisation with a track record of conducting arts programmes for stroke and brain injury survivors, developed SO, a performance-based arts programme with continued consultation from stakeholders (including stroke survivors). SO provides an opportunity for those who have had a stroke or brain injury to share their experiences with an audience through movement, music, songwriting and the spoken word.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, SHAPER has three primary aims: (1) to successfully embed each of the art interventions into the healthcare system (ie, taking a social prescribing approach), (2) to scale up these interventions at a larger scale and (3) to facilitate these interventions being commissioned by Clinical Commissioning Groups (CCGs), ensuring the long-term sustainability of delivery. 15 Stroke Odysseys Rosetta Life, a well-established non-profit organisation with a track record of conducting arts programmes for stroke and brain injury survivors, developed SO, a performance-based arts programme with continued consultation from stakeholders (including stroke survivors). SO provides an opportunity for those who have had a stroke or brain injury to share their experiences with an audience through movement, music, songwriting and the spoken word.…”
Section: Open Accessmentioning
confidence: 99%
“…SO is part of the Scaling-up Health Arts Programme: Implementation and Effectiveness Research (SHAPER), which is, to our knowledge, the world’s largest study on arts and health examining both clinical effectiveness and implementation effectiveness of three community-based arts programmes: Melodies for Mums (M4M), a singing intervention for postnatal depression, PD-Ballet, a dance intervention for Parkinson’s Disease and SO. Overall, SHAPER has three primary aims: (1) to successfully embed each of the art interventions into the healthcare system (ie, taking a social prescribing approach), (2) to scale up these interventions at a larger scale and (3) to facilitate these interventions being commissioned by Clinical Commissioning Groups (CCGs), ensuring the long-term sustainability of delivery 15…”
Section: Introductionmentioning
confidence: 99%
“…Other music interventions - not lead by a professional music therapist - such as group drumming have been very effective, leading to the enhancement of psychological states, specifically fewer depressive symptoms and greater social resilience ( Fancourt et al., 2016 ): there is a growing body of evidence demonstrating the effects of community group on mental health ( Estevao et al., 2021 ; Clift and Morrison, 2011 ; Coulton et al., 2015 ). For example, a study conducted with mothers suffering from postnatal depression found that mothers with moderate-severe depressive symptoms who participated in 10 weeks of music and singing classes with their babies had a significantly faster improvement in symptoms than mothers who participated in usual care groups ( Fancourt and Perkins, 2018 ).…”
Section: Music Music Therapy and Mental Healthmentioning
confidence: 99%
“…The current protocol reports the design and evaluation of the 'Scale-up of Health-Arts Programmes Effectiveness-Implementation Research' (SHAPER-Implement)part of a larger programme (referred to as 'SHAPER' 6 aimed at investigating ways to implement and deliver arts interventions at scale. We focus on two different health conditions: postnatal depression (PND) and Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%